2022
DOI: 10.3390/ani12233270
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptomic and Proteomic of Corynebacterium pseudotuberculosis Infection in the Spleen of Dairy Goats

Abstract: Corynebacterium pseudotuberculosis (C. pseudotuberculosis) is a zoonotic chronic infectious disease. It mainly occurs in dairy goats reared in herds, and once it invades the dairy goats, it is difficult to completely remove it, causing great harm to the development of the sheep industry. This study mainly was based on TMT-based quantitative proteomics and RNA-seq methods to measure the spleen samples of infected dairy goats at different time periods. Nine four-month-old dairy goats were divided into three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The results obtained indicated that C. pseudotuberculosis infection can impair immune response mechanisms and induce immune cell death [ 73 ]. Further proteome analyses of the spleen of dairy goats infected with C. pseudotuberculosis for different time periods indicated the adaptation of the host animals to the bacteria [ 74 ].…”
Section: Relevance and Properties Of Toxigenic Corynebacteriamentioning
confidence: 99%
“…The results obtained indicated that C. pseudotuberculosis infection can impair immune response mechanisms and induce immune cell death [ 73 ]. Further proteome analyses of the spleen of dairy goats infected with C. pseudotuberculosis for different time periods indicated the adaptation of the host animals to the bacteria [ 74 ].…”
Section: Relevance and Properties Of Toxigenic Corynebacteriamentioning
confidence: 99%
“…The formation of pyogranulomas, which are characteristic of C. pseudotuberculosis infection, involves both humoral and cell-mediated immunity, a complex process that requires the activation of macrophages and T lymphocytes [ 18 , 19 , 20 ]. Recent advances in high-throughput genomic technologies have enabled the first comprehensive profiling of the goat spleen transcriptome and proteome in response to experimental infection with Cp [ 21 , 22 , 23 ]. Currently, genome-wise approaches and the generation of big data are considered promising selection-associated techniques that can provide animal farming industries with the ability to cope with the issues caused by diseases through breeding for health traits [ 24 ].…”
Section: Introductionmentioning
confidence: 99%